2020
DOI: 10.33160/yam.2020.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Improvement Effect of 5-Aminolevulinic Acid on Hyperlipidemia in Miniature Schnauzer Dogs: An Open Study in 5 Cases of One Pedigree

Abstract: This is the first study to examine the long-term effect of 5-aminolevulinic acid mainly on serum lipoproteins in dogs with hyperlipidemia. We studied 5 Miniature Schnauzer cases whose fasting serum total triglyceride and very-low-density lipoprotein of triglyceride levels were extremely high (635 ± 116 and 520 ± 92 mg/dL, respectively). Although the total cholesterol values were normal, the very-low-density lipoprotein of cholesterol level was high (49 ± 7 mg/dL). Each dog received a 5-aminolevulinic acid supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…After Nishikawa et al established a mass production method of 5-ALA using bacteria ( 19 ), the effectiveness of 5-ALA was confirmed in not only agriculture, but also in medical and biological fields. 5-ALA is inexpensive, and it is practically used as a supplement to improve animal performance and immune response in the field of veterinary medicine ( 14 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…After Nishikawa et al established a mass production method of 5-ALA using bacteria ( 19 ), the effectiveness of 5-ALA was confirmed in not only agriculture, but also in medical and biological fields. 5-ALA is inexpensive, and it is practically used as a supplement to improve animal performance and immune response in the field of veterinary medicine ( 14 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 5-ALA is more efficiently utilized by the body when administered in combination with sodium ferrous citrate (5-ALA/SFC) [ 22 ]. 5-ALA has several bioactive effects, including antiviral [ 20 ] and immunomodulatory effects [ 7 ], and its usefulness has also been reported in veterinary practice, such as the application of PpIX in the diagnosis of malignant tumors [ 21 ] and efficacy in treating lipid metabolism disorders in dogs [ 27 ].…”
mentioning
confidence: 99%